Factores de competencia de las áreas metropolitanas Sobre la crisis del hecho metropolitano como factor de competencia (2004)
Legitimacy and constitutionality problems facing law 128 of 1994 become sharper when confronting it with what is conceived in the Political Constitution, since what has been prescribed in the aforementioned organic law enables competition factors of the metropolitan areas to be extended limitlessly till occupying the entire power enclosure of the associated municipalities, although the aforementioned law aimed at founding –unsuccessfully– the concept of metropolitan fact as a delimiting factor cosmopolitan competition. This risk of emptying the municipal competitions is growing bigger, since those areas can assume the environmental authority over their municipalities, a fact which although might reinforce the municipal autonomy involved there once the associative character of the areas is revealed, in practice it has been consolidating the pre–domain of the “nucleus” city mayor, in detriment of the other municipalities’ autonomy.